KEPUASAN PESERTA DIDIK DALAM PEMBELAJARAN DARING PADA POKOK BAHASAN MOMENTUM DAN IMPULS DI SMA NEGERI 4 KOTA JAYAPURA - Tuhusula, Trieana S.; Lumbu, Albert; Lasmono, Paulus G. D. (Universitas Cenderawasih, 2024)
This study aims to determine the relationship, and the effect of student satisfaction in online learning on student learning outcomes. This type of research is descriptive quantitative research. Data collection techniques used are tests and questionnaires. The data obtained were then analyzed using SPSS 16 and Microsoft Excel programs. The research was carried out at SMA Negeri 4 Jayapura for the academic year 2020/2021. The population of students is class X. The research sample is class X IPA 5 with a total sample of 32 students. In the general percentage results obtained 72% of students are satisfied with online learning.from the dimension tangible, 81% of students were satisfied. However, for thedimension assurance, 67% of students were satisfied. In the dimension empathy, 72% of students are satisfied and for the dimension reliability, the percentage figure shows 60% of students are satisfied. And on the dimension of responsiveness, 70% of students are satisfied.